Voids/Cement Ratio Controlling Tensile Strength of Cement-Treated Soils - Nilo Cesar Consoli (2011)
The improvement of locally available soils with cement can provide great advantages, including avoiding the need to borrow volumes of appropriate material and disposing of the local soil in deposits. This research aims to quantify the influence of the amount of cement, the porosity, and the voids/cement ratio in the assessment of splitting tensile strength (q(t)), also known as indirect diametrical tensile (IDT) strength, of three distinct soils from Brazil and Portugal. From Brazil, clayey sand derived from Botucatu sandstone and uniform Osorio sand were considered; from Portugal, silty sand derived from weathered Porto granite was studied. A number of splitting tensile strength tests were carried out. The results show that q(t) increased with the amount of cement (C) and decreases in porosity (eta) for the three soil-cement mixtures. A power function was well-adapted to fit both q(t)-C and q(t)-eta. Finally, the tensile strength was plotted against the porosity/volumetric cement content relationship (eta/C(iv)), in which volumetric cement content is adjusted by a different exponent depending on the soil (0.21 for Porto silty sand-cement mixtures, 0.28 for Botucatu clayey sand-cement mixtures, and 1.0 for Osorio sand-cement mixtures). These plots show unique correlations for each soil-cement mixture, indicating that the index property is a good parameter in the evaluation of the splitting tensile strength of the soils studied. As a consequence, for each of the three soil-cement mixtures studied, a target q(t) value could be obtained by both porosity reduction and cement increase. This experimental framework will enable a good definition of the mechanical parameters used in the design of foundations and subgrades of railways platforms, whose system failure mechanisms usually start under tensile stresses at the base of the improved layer, and in the execution quality control of such earthworks. DOI: 10.1061/(ASCE)GT.1943-5606.0000524. (C) 2011 American Society of Civil Engineers.